Molecular characterization of rotavirus in oysters from Oualidia lagoon in Morocco: Characterization of rotaviruses in mollusks - Hatib, Abderrahim; Boussettine, Rihabe; Hassou, Najwa; Benani, Abdelouaheb; Ennaji, Moulay Mustapha (Cellular and Molecular Biology, 2022)
Group A rotavirus (RVA) is the most important foodborne pathogen and is transmitted by oysters. The purpose of this study was to monitor and evaluate the prevalence of RVA in oysters collected in Oualidia Lagoon, Morocco from March 2018 to March 2019 and its relationship to watershed contribution. To achieve this, 312 oysters from 26 lots were collected and tested for viral contamination using real-time polymerase chain reaction. The results showed that 46.15% of the tested samples were positive for RVA. The seasonal distribution of RVA was statistically significant. This is a warning signal against the potential health risks in this oyster growing area, following the consumption of oysters contaminated with RVA, which presents a huge threat to human health resulting in serious illnesses of gastroenteritis.